Workshop Diagnosis of Escherichia coli on Well Water Samples - Krisdianilo, Visensius; Vincentia Ade Rizky; Saadah Siregar; Rahayu, Asvia (JURNAL PENGMAS KESTRA (JPK), 2023)
Diarrhea is an endemic disease in Indonesia and is also a disease that can potentially cause extraordinary events that are often accompanied by death. Escherichia coli is a commensal bacterium, intestinal pathogen and extraintestinal pathogen that can cause urinary tract infections, meningitis, and septicemia. Most of the E. coli bacteria are in the digestive tract of animals as well as humans and are normal flora, but some are pathogenic that can cause diarrhea in humans (Bettelheim, 2000). Water is very potential in the spread of various diseases, for example water contaminated by pathogens and drunk by humans can cause disease (water born disease). Food and water contamination has been identified as a potential source of the spread of Escherichia coli pathogenicity in humans. The method has the disadvantage of taking a long time, a large number of samples, and an incorrect reading method of results. PCR technique is one of the molecular techniques used to identify infectious diseases caused by Escherchia coli. This method has many advantages that can produce accurate, fast, specific product amplification, requiring a small number of samples. and this method can be used to overcome the weaknesses of conventional diagnostics (cultures). The purpose of this study was to socialize the detection of Escherichia coli bacteria in well water samples by culture and PCR methods. From the examination that has been done obtained the results of cultural examination obtained colonies that grow on the medium Mac Conkey To appear round, flat edges, smooth surface with the color of the colony, then the results of pcr examination obtained 239 bp, which means bacteria found from the isolation of well water samples in the bottom of the identic pakam with Escherichia coli.As well as workshop participants can follow and understand the materials submitted and also the examination procedures carried out.